Persuasive Language in Indonesian Political Campaign Slogans of the 2024 Election: A Critical Discourse Analysis - Gigih Ariastuti Purwandari; Kristianto Setiawan; Indah Puspitasari; Lely Tri Wijayanti (Haumeni Journal of Education, 2025)
This study examines the persuasive language employed in political campaign slogans of the 2024 legislative election in Banyumas District, Indonesia. Using Critical Discourse Analysis (CDA) (Fairclough, 2015; van Dijk, 1997), the research analyzes 20 campaign slogans collected from posters and billboards of prospective legislative candidates from 18 political parties. The study aims to identify linguistic strategies, analyze how slogans construct political meaning, and explore the reflection of ideology and local culture. The findings show that candidates predominantly use imperative directives, emotive/moral appeals, local dialects, and credibility-based statements. These strategies function to mobilize voters, build trust, and reflect ideological and cultural identities